Comparative Analysis of Implementation of Murabahah Bil Wakalah Contracts and Musyarakah Mutanaqisah Contracts for Sharia Financing Products - Intansari, Anggita Isty; Fatimah (Faculty of Islamic Economics and Business, UIN Prof. K. H. Saifuddin Zuhri Purwokerto, 2022)
A home is a basic human need that plays an important role in the continuation of human life. The problem of housing and settlement has existed and will continue to exist in response to population growth, demographics and socio-economic needs. The high demand for housing and population growth provide opportunities for Islamic financial institutions to provide products that help people purchase housing. The purpose of this study is to determine the application of the Murabaha Contract and the Musharaka Mutanaqisah Contract and find a comparison of her two contracts in Islamic KPR funding. Knowing the mechanism and type of research represents field research. This research was conducted using qualitative methods with a descriptive approach. As a result of the research and analysis, it was found that the application of the Murabaha Bil Wakala Convention takes precedence over the Musharaka Mutanaqishah Convention. A comparison of the two loan agreements can then be viewed in terms of similarities and differences between the two agreements.